Peningkatan Keterampilan Menggunakan Teknologi Pembelajaran Bagi Ikatan Guru Bahasa Daerah Kota Parepare - Yusring Sanusi Baso; Fadlan Ahmad; Faridah Rahman; Andi Agussalim; Najmuddin H. Abd. Safa (Khazanah Pengabdian, 2020)
The object (target audience) of this service is the Regional Language Teachers Association (IGBD) of the city of Parepare. Partner issues raised by the community service team include regional language teachers often having difficulty engaging students in the local language learning process. This is due to the competence of regional language teachers that are still conventional in the sense that they do not involve learning technology media. In connection with this condition, the head of the Unhas community service team offered training in the use of local language learning technology to provide the latest technology utilization skills in learning. The method used is the Fishball Discussion Forum (FDF), Collaborative Learning (CL) and Experiential Learning (EL). This dedication has provided the use of the latest learning technology skills, the application of innovative regional language learning methods. This dedication has resulted in a book titled Innovative Models of Regional Language Retention. In short it can be said that this dedication has succeeded in opening up the insights of the participants to always actively use the latest interactive learning methods and involve students in the learning process.